2007
DOI: 10.1016/j.yjmcc.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/Reoxygenation of isolated rat heart mitochondria causes cytochrome c release and oxidative stress; evidence for involvement of mitochondrial nitric oxide synthase

Abstract: The objective of the present study was to delineate the molecular mechanisms for mitochondrial contribution to oxidative stress induced by hypoxia and reoxygenation in the heart. The present study introduces a novel model allowing real-time studying mitochondria under hypoxia and reoxygenation, and describes the significance of intramitochondrial calcium homeostasis and mitochondrial nitric oxide synthase (mtNOS) for oxidative stress. The present study shows that incubating isolated rat heart mitochondria unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 47 publications
(72 reference statements)
1
57
0
Order By: Relevance
“…However, this hypothesis is very difficult to explain, as NO production can be significantly decreased by preventing mitochondrial Ca 2 þ uptake. Recently, Ghafourifar and his colleagues have reported that hypoxia/ reoxygenation and tamoxifen can elevate [Ca 2 þ ] m by increasing mitochondrial calcium uptake and the release of [Ca 2 þ ] m from the granules in mitochondria, and stimulate mtNOS to generate NO Zenebe et al, 2007). By inhibiting mitochondrial calcium uptake with RR, we found that the relative fluorescence intensity of NO significantly decreased in postirradiated r þ A L cells ( Figure 3B).…”
mentioning
confidence: 51%
“…However, this hypothesis is very difficult to explain, as NO production can be significantly decreased by preventing mitochondrial Ca 2 þ uptake. Recently, Ghafourifar and his colleagues have reported that hypoxia/ reoxygenation and tamoxifen can elevate [Ca 2 þ ] m by increasing mitochondrial calcium uptake and the release of [Ca 2 þ ] m from the granules in mitochondria, and stimulate mtNOS to generate NO Zenebe et al, 2007). By inhibiting mitochondrial calcium uptake with RR, we found that the relative fluorescence intensity of NO significantly decreased in postirradiated r þ A L cells ( Figure 3B).…”
mentioning
confidence: 51%
“…Peroxynitrite is a powerful oxidative NO congener that irreversibly inhibits the activity of various mitochondrial proteins including COX (7,17). Uric acid is a well-known peroxynitrite scavenger (17) that protects against peroxynitrite-induced damaging mitochondrial components (10,18). As shown in Figure 2A, uric acid dose-dependently protected the irreversible COX inactivation induced by NO.…”
Section: Discussionmentioning
confidence: 97%
“…Those include mitochondrial superoxide dismutase that removes superoxide, one of the two precursors of peroxynitrite. Additionally, mitochondria contain large quantities of reduced glutathione that neutralizes peroxynitrite to S-nitrosating species that exert reversible interaction with mitochondrial components (10). Thus, those protective mechanisms preserve the reversibility of COX inhibition by NO via decreasing the probability of peroxynitrite formation or neutralizing the peroxynitrite formed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations